2003
DOI: 10.1021/ma034763t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, Biodegradation, and in Vitro Photodynamic Activities of Silicon(IV) Phthalocyanines Conjugated Axially with Poly(ε-caprolactone)

Abstract: A new series of phthalocyanine-containing biodegradable poly(ε-caprolactone)s have been synthesized by ring-opening polymerization of ε-caprolactone and/or 5-ethylene ketal ε-caprolactone using silicon phthalocyanine dihydroxide as the initiator and tin(II) 2-ethylhexanoate as the catalyst. The polymers have been spectroscopically characterized, and their molecular weights have been determined by gel permeation chromatography (GPC). All the polymers exhibit typical electronic absorption and fluorescence charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…The aggregation tendency of the dendritic phthalocyanines decreases as the size of the dendrons increases [9][10][11][12][13]; however, it is very difficult to realize catalyst recovery and recycling by this method. The strategy of immobilizing MtPc on selected insoluble supports (such as activated charcoal, zeolite or clay) has been introduced and used to prepare polymeric MtPc catalysts and thereby to facilitate catalyst separation and recycling, which reduces effluent contamination [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The aggregation tendency of the dendritic phthalocyanines decreases as the size of the dendrons increases [9][10][11][12][13]; however, it is very difficult to realize catalyst recovery and recycling by this method. The strategy of immobilizing MtPc on selected insoluble supports (such as activated charcoal, zeolite or clay) has been introduced and used to prepare polymeric MtPc catalysts and thereby to facilitate catalyst separation and recycling, which reduces effluent contamination [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Upon excitation at 671 nm, 5-7 exhibited a fluorescence emission peak at λ = 711, 710 and 712 nm, respectively, with a Stokes shift of 0-2 nm, near the fluorescence emission peak of 4 at λ = 710 nm. It can be concluded that under the polymerization conditions in this study, the luminescence property of the phthalocyanine core is protected[36,57,58]. As in electronic spectra case, the fluorescence intensity decreased with increasing [M]/[I] ratio, probably due to the decrease of the percentage of the phthalocyanine core in the total sample solution.…”
mentioning
confidence: 59%
“…In the UV-vis absorption spectra of 4-7, Q-band absorptions were observed as a single narrow band of high intensity at 705, 705, 704 and 703 nm, respectively, with shoulders at a slightly higher energy side of the Q band, typical for non-aggregated phthalocyanines. The Q-band absorption values did not significantly change for the whole series of ZnPc-containing star polymers 5-7, which suggested that the length of the polymeric substituent does not significantly perturb the π-electron system[36,67]. InFig.…”
mentioning
confidence: 82%
See 2 more Smart Citations